DOKUMEN MUTU DALAM SISTEM PENJAMINAN MUTU PENDIDIKAN ISLAM: KONSEP DAN INTEGRASI BUDAYA ORGANISASI - Rahmi Sari; Elvarisna Elvarisna; Jamilus Jamilus (Jurnal Manajemen Pendidikan, 2025)
Quality documents are an important component in ensuring that the implementation of Islamic education runs according to the set standards. However, the effectiveness of a quality document is greatly influenced by the extent to which it is aligned with the organizational culture that underpins the institution's values and practices. This article analyzes the urgency of integrating organizational cultural maps in Islamic education quality documents through a qualitative approach based on literature studies. The results of the study show that the alignment between quality documents and organizational culture can strengthen the consistency of standard implementation, increase the commitment of school residents, and facilitate the evaluation process and continuous improvement. This integration also helps institutions build a distinctive quality identity rooted in Islamic values. The findings of this study contribute to the development of more effective quality assurance strategies, while encouraging Islamic educational institutions to optimize their roles through professional, adaptive, and quality-oriented governance.